Recurrent gene amplification and soft selective sweeps during evolution of multidrug resistance in malaria parasites. - Nair, S; Nash, D; Sudimack, D; Jaidee, A; Barends, M; Uhlemann, A; Krishna, S; Nosten, F; Anderson, T (2007)
When selection is strong and beneficial alleles have a single origin, local reductions in genetic diversity are expected. However, when beneficial alleles have multiple origins or were segregating in the population prior to a change in selection regime, the impact on genetic diversity may be less clear. We describe an example of such a "soft" selective sweep in the malaria parasite Plasmodium falciparum that involves adaptive genome rearrangements. Amplification in copy number of genome regions containing the pfmdr1 gene on chromosome 5 confer resistance to mefloquine and spread rapidly in the 1990s. Using flanking microsatellite data and real-time polymerase chain reaction determination of copy number, we show that 5-15 independent amplification events have occurred in parasites on the Thailand/Burma border. The amplified genome regions (amplicons) range in size from 14.7 to 49 kb and contain 2-11 genes, with 2-4 copies arranged in tandem. To examine the impact of drug selection on flanking variation, we genotyped 48 microsatellites on chromosome 5 in 326 parasites from a single Thai location. Diversity was reduced in a 170- to 250-kb (10-15 cM) region of chromosomes containing multiple copies of pfmdr1, consistent with hitchhiking resulting from the rapid recent spread of selected chromosomes. However, diversity immediately flanking pfmdr1 is reduced by only 42% on chromosomes bearing multiple amplicons relative to chromosomes carrying a single copy. We highlight 2 features of these results: 1) All amplicon break points occur in monomeric A/T tracts (9-45 bp). Given the abundance of these tracts in P. falciparum, we expect that duplications will occur frequently at multiple genomic locations and have been underestimated as drivers of phenotypic evolution in this pathogen. 2) The signature left by the spread of amplified genome segments is broad, but results in only limited reduction in diversity. If such "soft" sweeps are common in nature, statistical methods based on diversity reduction may be inefficient at detecting evidence for selection in genome-wide marker screens. This may be particularly likely when mutation rate is high, as appears to be the case for gene duplications, and in pathogen populations where effective population sizes are typically very large.